IMPROVING THE WELFARE OF FAMILIES IN RUSSIA: STATE AND REGIONAL ASPECT - O. Makhalina; V. Makhalin (Вестник университета, 2019)
The article briefly considers the current economic state of the family in the Russian Federation, analyzed the activities for social support and improved well-being of families and proposed measures to support and meet the interests of the families, increasing their economic independence.